Perfil e fatores associados à descompensação da cirrose em pacientes internados em um hospital terciário na região Sul do Brasil - Caurio, Caroline Canabarro (2020)
Liver cirrhosis is a highly prevalent disease, which develops in its natural history complications that adds high morbidity and mortality. Progresses have been made to better understand its pathophysiology and thereby offer more appropriate treatments to patients, as well as to understand the moment of ceasing resources. We know little about the prevalence of these patients' care at the public system in our region. The aim of our study was to describe the epidemiological profile of patients admitted to the Gastroenterology Service of Hospital Universitário de Santa Maria (HUSM), with an emphasis on cirrhotic patients and the analysis of their complications and associated mortality. To this end, a cross-sectional, descriptive and retrospective analytical study was developed through the analysis of medical records from patients diagnosed with liver cirrhosis admitted from January 2014 to December 2018 at the Gastroenterology service of HUSM. For data collection, we created a form, which evaluated the following variables: gender, age, reason for hospitalization, complications during hospitalization, laboratory tests for the classification of Child-Pugh-Turcotte, etiology of cirrhosis, comorbidities and in-hospital mortality. The sample consisted of an analysis of 221 hospitalizations due to cirrhosis at the Gastroenterology service of HUSM, Santa Maria, Rio Grande do Sul (RS). The data were evaluated using descriptive statistics (absolute and relative frequencies). Associations were verified using Chi-square or Fisher's exact tests. The level of significance adopted was 5%. Results: The mean age observed in patients was 56 ± 13.7, with the majority being male (80.2%). They had Child-Pugh B or C in 24.9% and 25.8% of cases, respectively, which was positively related to death, and the predominant etiology of liver disease was alcoholic (66.7%). The most frequent reason for hospitalization was ascites (52.5%), followed by upper gastrointestinal bleeding (47.5%) and hepatic encephalopathy (44.5%). Infection was responsible for 21.7% of the reasons for hospitalization, which had a positive association with death, and spontaneous bacterial peritonitis was the most frequent site of infection (8.1%). The most prevalent complications during hospitalization were acute kidney injury (20.8%), infections (20.4%), hepatic encephalopathy (19.9%), and ascites (19%). In our study, all in-hospital complications, except ascites, were associated with higher mortality. We conclude that hospitalizations due to cirrhosis had alcoholism as the main etiology, followed by HCV infection. There was a significant association between in-hospital mortality and decompensated cirrhosis due to infection.